O incentivo à leitura e seus impactos: o Programa SESI Cidadania e a Biblioteca do Morro do Andaraí - Gaspar, Gabriel Gonçalves (2018)
The present study proposed to investigate the impacts generated in the community after the inauguration of the Morro do Andaraí library. It describes and analyzes who the social actors are behind this cultural equipment, analyzing the interests that are at stake in that territory; the complex dynamics among the residents, the police and the library are also described and analyzed, based on the fieldwork developed. From the theoretical basis, direct observations, and semi-structured interviews with the children who attend the space and the professionals who work there, we sought to understand the dynamics that occur for the daily construction of the library. The results of the study indicate that there is a precariousness regarding space management, and consequently of the UPPs project, however, through the narratives of the children interviewed, one can perceive the benefits that the library generates for the community; benefits that go far beyond reading and produce greater access to services and information that are fundamental to citizenship; it was also possible to verify the appropriation that the children developed with the space, through several non-programmed uses of the library.